7823 11-Keto Testosterone Throughout Life - Walravens, Joeri; Reyns, Tim; Cools, Martine; Fiers, Tom; Lapauw, Bruno (Journal of the Endocrine Society, 2024)
Abstract Disclosure: J. Walravens: None. T. Reyns: None. M. Cools: None. T. Fiers: None. B. Lapauw: None. Introduction: 11-oxygenated androgens are implicated in several disorders of androgen excess such as premature adrenarche, PCOS and CAH. These steroids may be more useful markers than traditional androgens to follow disease progression and treatment in such disorders. However, most research focusses on 11-oxygenated androgen levels in adult life. Little is known about 11-oxygenated androgen levels in childhood and adolescence. Furthermore, no widely accepted reference ranges exist for these steroids, limiting their clinical use. To overcome some of these issues, we report 11-keto testosterone (11KT) levels throughout life with their reference ranges. Objective: To determine the changes in 11KT serum levels in men and women throughout life and establish corresponding reference ranges. Methods: Steroid levels were determined in 13600 in- and outpatients using the steroid panel at Ghent University Hospital. This steroid panel includes 15 steroids, among which testosterone, androstenedione, pregnenolone (preg), DHEA, cortisol and 11KT. Data were stratified according to sex and age category: per 3 years in individuals from 0 to 18 years and per decade in adults. Extreme outliers for testosterone, androstenedione, DHEA and cortisol were removed per age and sex category. Afterwards, 11KT 90% reference ranges were established for apparently healthy individuals using the refineR-package for RStudio. DHEA and preg were included in the analysis as adrenal steroid controls. Finally, reference ranges were LOESS-smoothed across age categories to reduce effects of varying sample sizes. Results: In men, 11KT levels increase linearly from 0-2 years from a median of 8.0 (90% reference range: 1.2-48.2) ng/dL in early life to a peak of 36.5 (14.0–91.3) ng/dL at 15-18 years. Afterwards, 11KT levels decrease at 5% per 10 years to 24.2 (6.9-53.7) ng/dL in the age category of 70-79. In women, 11KT levels increase from 19.0 (2.3-45.1) ng/dL from 0-2 years to 29.1 (11.0-75.1) ng/dL at 15 to 18 years. Afterwards, 11KT levels remain constant until 60 to 69 years where 11KT levels quickly decrease to 21.6 (8.8-46.8) ng/dL at ages 70 to 79.In both men and women, DHEA and preg reached peak concentrations later than 11KT at ages of 20 to 29, after which concentrations decreased faster per 10 years (DHEA: 25%, preg: 16%). Conclusion: Our results show differences between the course of 11KT levels and other steroids. Compared to DHEA and preg, 11KT levels peak earlier in life, between 15 and 18 years, as compared to around 20-29 years and decrease at a slower rate. Additionally, 11KT levels peak earlier than total testosterone levels (15-18 vs ±30 years) and decline at a slower pace (5%/10 years vs. 10-20%/10 years). This larger difference compared to testosterone can likely be attributed to the adrenal synthesis of 11KT, as opposed to the gonadal synthesis of testosterone, supporting its potential as a marker of adrenal disorders in men. Presentation: 6/3/2024